Lessons from Japanese development : an analytical economic history - Kelley, Allen C.; Williamson, Jeffrey G. (Chicago : University of Chicago Press, 1974)
The book attempts to explain Japanese economic development during a critical phase in her history-from the 1880s to the beginning of World War 1.
Includes index.
Includes bibliographical references: p. 263-277
usc 14/01/2019
Loans
Keywords: Economic history; Economic development; Japan